Lumbar flexion relaxation phenomenon in the patients with acute and subacute mechanical low back pain and normal subjects - Desai, Hetal Sanjay; Bisen, Rahul Singh (International Journal of Research in Medical Sciences, 2017)
Background: The purpose is to examine the myoelectrical activity of erector spinae muscle in patients with acute and sub-acute mechanical low back pain (MLBP) and normal subjects. Methods: A total of 30 patients 15 with MLBP and 15 normal subjects of both genders participated in the study with convenient sampling; all were aged between 20-50 years. The participants were asked to perform movement which was paced by computer running a program and the myoelectrical activity of erector spinae muscle in patients with acute and sub-acute mechanical low back pain and normal subjects were examined. Results: This study stated that patients with MLBP has increased or over activity of erector spinae muscle during complete lumbar flexion when the muscle should be electrically silent. This was observed with help of EMG graph where increase in activity was observed with increase in amplitude, duration and time in graph. Conclusions: There is increase in the amplitude, duration and time in flexion relaxation phenomenon (FRP) in mechanical low back pain patients when compared to normal subjects.